Adopting television as a new channel for e-commerce. The influence of interactive technologies on consumer behavior - Blasco-Arcas, Lorena; Hernandez-Ortega, Blanca; Jimenez-Martinez, Julio (Electronic commerce research, 2013)
The aim of this research is twofold. Firstly, it analyzes how the two main features of Internet Protocol Television (IPTV), interactivity and personalization, influence both customers’ perceived performance and involvement with a web-based information service. Secondly, it studies whether personalization and interactivity improve customer purchase intentions of this service through IPTV. We developed a 2×2 between-subjects factorial design and applied MANOVA analyses. Findings verify that interactivity and personalization foster customer involvement with the service, perceived performance of IPTV and purchase intentions. Moreover, interactivity promotes the effect of personalization on perceived performance and customer involvement. This research concludes that customers’ involvement and purchase behavior are not derived exclusively from their relationship with the firm, but also from connections established in the channel with other customers. Customers also appreciate participating in the service provision process, so firms should promote personalization activities during the purchase in order to improve customers’ performance evaluation.